Analysis of the factors influencing on purchase decision ship ticket PT. Pelni (PERSERO) Surabaya branch - Qumairoh, Ernita Juniarti (Proceeding of International Management Conference and Progressive Papers, 2023)
The purpose of this study was to examine the factors that influence the decision to purchase PT Pelni (Persero) Surabaya ship tickets. This research uses a quantitative approach. The analysis technique used is factor analysis technique for variable data collection with exploratory method conducted on passengers of PT Pelni (Persero) Surabaya branch by distributing questionnaires to 50 respondents. This study uses the SPSS 26 for Windows program which is used to analyse the factors that influence purchasing decisions for purchasing PT Pelni (Persero) Surabaya ship tickets. The results of this study concluded that, the factors that influence consumer decisions to buy PT Pelni (Persero) ship tickets include 6 factors, namely: Facility factors, ease of ticket acquisition factors, departure location factors, service quality factors, ticket price factors and schedule accuracy factors. Of the 6 factors, the most dominant factor or the main factor influencing passenger purchasing decisions is the Facility factor which in this factor also represents 15 other variables. Keywords: purchase decision; Marketing mix strategy; Internal factors; Environmental factors